THE EFFECT OF NIGELLA SATIVA L. ON INTRACTABLE PEDIATRIC SEIZURES - AKHONDIAN MD, J.; PARSA MD, A.; RAKHSHANDE MD, H. (Iranian Journal of Child Neurology, 2009)
Background: Despite availability and administration of numerous antiepileptic drugs (AEDs) nearly 15% of childhood epilepsy cases are resistant to treatment; in traditional medicine however Nigella sativa L. (Black seed) has been known for its anticonvulsant effects. Materials and Methods: In this double-blind clinical trial conducted on children with refractory epilepsy we administered the aqueous extract of black seed as an adjunct therapy and compared the effects with those of a placebo. The study was performed between Sep 2003 and Nov 2004. The subjects received either extract or placebo for a period of four weeks and between these two periods for two weeks they received only their pre-existing anti-epileptic drugs (AEDs). Results: The mean frequency of seizures decreased significantly during treatment with extract, (p-value =0/007). Conclusion: It can be concluded that the water extract of Nigella sativa L. has antiepileptic effects in children with refractory seizures that do not respond to known AEDS. keywords: Nigella sativa, Intractable seizures, Children